The Effect of Anti Pollutant Gel from Sansevieria trifasciata on Malondialdehyde Level and Histopathology of Rats' Liver and Lungs Induced by Cigarette, Coal, and Mosquito Smoke - Irfan Kesumayadi; Luh Ayu Nanamy Khrisnashanti Eva Susila; Ericko Hartanto; Darmawati Ayu Indraswari (Universitas Gadjah Mada, 2020)
Gas pollutants that accumulate in the room with restricted air circulation may cause respiratory system disorders. A pregnane glycoside compound from Sansevieria can reduce the pollutants. This study aims at producing gels from Sansevieria extract to neutralize indoor gas pollutants. Sansevieria extract is produced by the maceration process with composition 8 g simplicia and 100 ml ethanol 96%. The extract was processed into the gel with a 20% concentration. The gel was applied to rats (Rattus norvegicus) Wistar strain induced by cigarette, coal, and mosquito smoke with positive control and treatment groups. After 8 days, the Gross examination and histopathology of lungs and liver were observed quantitatively. MDA levels were measured with the TBARS method. Data were analyzed by independent sample T-test and Mann-Whitney test with p-value considered significant if <0,05. Gross examination of lungs showed a significant difference between the treatment and control group that was induced by coal smoke (p=0.031), and mosquito smoke (p=0.006), and the liver's gross of cigarette smoke (p=0.040). Histopathology of lungs showed a significant difference in mosquito smoke (p=0.032) and no significant difference in histopathology of the liver. MDA levels showed significant difference in coal smoke (p=0.020) and mosquito smoke (p=0.000). In conclusion, anti pollutant gel reduces MDA levels and damage of the lungs induced by pollutants.